Effects of karate activities on the physical fitness status of first year college students in the University of Northern Philippines - Soliven, Schubert R. (Vigan City, Ilocos Sur : [s.n.], 2004)
The purpose of this study is to determine the effect of karate activities on the physical fitness status of the first year college students in UNP during the school year 2003-2004.
Bibliography: pages 35-36.
CHED-La Union
Keywords: Physical fitness; Physical education